2021
DOI: 10.37934/arfmts.89.1.6276
|View full text |Cite
|
Sign up to set email alerts
|

MHD Heat and Mass Transfer Steady Flow of a Convective Fluid Through a Porous Plate in The Presence of Diffusion Thermo and Aligned Magnetic Field

Abstract: In the presence of a diffusion thermal and coupled magnet field effect, this manuscript seeks continuous free convective motion by a viscous, incompressible fluid that conducts electrically past a sloping platform via a porous medium. The free flow speed may be compatible with the exponentially tiny disrupting law. Two-term harmonic and non-harmonic functions solve dimensional-less control equations analytically. Detailed graphs are used to determine the budgets for tempo, temperature, and concentration for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They found that the nanoparticles significantly improved the heat transfer process. Other recent studies related to the non-Newtonian nanofluid flow could be found in Kodi et al, [3][4][5][6], Vaddemani et al, [7], Kommaddi et al, [8] and Suresh Kumar et al, [9]. Rafique et al, [10] reported the increment of heat transfer rate by 1.135% for single walled carbon nanotubes (SWCNTs) and 1.275% for multi walled carbon nanotubes (MWCNTs) with the application of suction parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the nanoparticles significantly improved the heat transfer process. Other recent studies related to the non-Newtonian nanofluid flow could be found in Kodi et al, [3][4][5][6], Vaddemani et al, [7], Kommaddi et al, [8] and Suresh Kumar et al, [9]. Rafique et al, [10] reported the increment of heat transfer rate by 1.135% for single walled carbon nanotubes (SWCNTs) and 1.275% for multi walled carbon nanotubes (MWCNTs) with the application of suction parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Ganji et al [23] examined the entropy production on the Hagen-Poiseuille flow of viscous fluid within a circular pipe due to the variable viscosity and heat transfer. Numerous studies have been conducted on non-Newtonian fluids with heat and mass transfer under different effects and flows, in a porous medium and a magnetic field [24][25][26][27]. These studies have examined the impacts of pertinent parameters on concentration, velocity, volumetric flux and temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…Raghunath et al, [43] have analyzed Chemical reaction with aligned magnetic field effects on unsteady MHD Kuvshinski fluid flow past an inclined porous plate in the presence of radiation and Soret effects. Obulesu et al, [44] have discussed MHD Heat and Mass Transfer Steady Flow of a Convective Fluid through a Porous Plate in The Presence of Diffusion Thermo and Aligned Magnetic field.…”
Section: Introductionmentioning
confidence: 99%